Histamine dihydrochloride for the treatment of acute myeloid leukemia, malignant melanoma and renal cell carcinoma - Dengler, Jolanta; Ho, Anthony Dick (Future oncology, 2008)
Histamine dihydrochloride is a vasoactive biogenic amine. It inhibits the reactive oxygen species formation in monocytes via histamine H2 receptors and protects natural killer and T cells from oxidative damage. Histamine has the potential to optimize cytokine-induced activation of T cells and natural killer cells; therefore, the addition of histamine to cytokine treatment may improve treatment efficacy. Clinical trials in solid tumors and in acute myeloid leukemia have demonstrated the potential to improve treatment outcome when histamine dihydrochloride is combined with immunotherapy. In patients with metastatic malignant melanoma, this strategy improved remission rates and increased survival. On the other hand, less promising results were reported for histamine dihydrochloride added to cytokines in patients with other solid tumors, especially in advanced renal cell carcinoma. A recent international Phase III trial performed in 320 patients showed that maintenance therapy with histamine dihydrochloride and IL-2 was able to improve leukemia-free survival in patients with acute myeloid leukemia, without an effect on overall survival. The combination of histamine dihydrochloride with IL-2 potentially offers an efficacious and tolerable maintenance strategy for patients with acute myeloid leukemia; however, its impact on survival remains to be explored.